Susceptibility to advanced age-related macular degeneration and alleles of complement factor H, complement factor B, complement component 2, complement component 3, and age-related maculopathy susceptibility 2 genes in a Mexican population - Buentello-Volante, Beatriz; Rodriguez-Ruiz, Gabriela; Miranda-Duarte, Antonio; Pompa-Mera, Ericka N; Graue-Wiechers, Federico; Bekker-Méndez, Carolina; Ayala-Ramirez, Raul; Quezada, Carlos; Rodríguez-Loaiza, Jose L; Zenteno, Juan C (Molecular vision, 2012)
To investigate the association of age-related macular degeneration (AMD)-high risk alleles of the complement factor H (CFH), complement factor B (CFB), complement component 2 (C2), complement component 3 (C3), and age-related maculopathy susceptibility 2 (ARMS2) genes in a Mexican population for the first time. Genotyping was performed for the Y402H variant of CFH, for the L9H, R32Q, and K565E variants of CFB, the E318D variant of C2, the A69S variant of ARMS2, and the R102G variant of C3 in 159 Mexican mestizo patients at advanced stages of AMD, i.e., CARMS (Clinical Age-Related Maculopathy Staging System) grade 4 or 5. The frequency of these variants was also investigated in a group of 152 control subjects without AMD. Genomic DNA was extracted from blood leukocytes, and genotyping was performed using PCR followed by direct sequencing. Allele-specific restriction enzyme digestion was used to detect the R102G polymorphism in C3. There were significant differences in the allelic distribution between the two groups for CFH Y402H (p=1×10(-5)), ARMS A69S (p=4×10(-7)), and CFB R32Q (p=0.01). The odds ratios (95% confidence interval) obtained for the risk alleles of these three variants were 3.8 (2.4-5.9), 3.04 (2.2-4.3), and 2.5 (1.1-5.7), respectively. Haplotype analysis including the two most significantly associated alleles (CFH Y402H and ARMS A69S) indicated that the C-T combination conferred an odds ratio (95% confidence interval) of 6.9 (3.2-14.8). The exposed attributable risk for this particular haplotype was 85.5%. This is the first case-control investigation of AMD-high risk alleles in a Latino population. Our results support that CFH, ARMS2, and CFB AMD-risk alleles are consistently associated with the disease, even in ethnic groups with a complex admixture of ancestral populations such as Mexican mestizos.